Medida de segurança em tratamento ambulatorial no contexto da reforma psiquiátrica - Sacchetin, Beatriz Ferruzzi (2021)
The people submitted to security measures suffer from severe processes of invisibility in criminal policies, health policies and in the scope of scientific production. Regarding the modality of hospitalization, there are important complaints that point to violations of the fundamental rights of these people, due to the imposition of treatment in deprivation of liberty, contrary to the proposal for deinstitutionalization. In the opposite direction, the ambulatorial treatment of the security measure proposes an intervention executed in physical liberty for these subjects and, for this reason, it was verified whether this modality would be a viable alternative for the application of the measure from the perspective of the Psychiatric Reform. Thus, the research aimed to collect data about the ambulatorial measure, its fundamentals, procedures, treatment execution, including the institutions in which they occur and the flow of the service, and to analyze them in the light of the guidelines of the Psychiatric Reform. Based on an interdisciplinary bibliography, an empirical research was carried out, collecting quantitative data from the city of São Paulo/SP and interviews with subjects submitted to ambulatorial security measures and professionals from an institution in the countryside of the state of São Paulo. The work considered aspects regarding the theme in the scope of mental health, comprising the different models of care, the background, trajectories and guidelines of Psychiatric Reform, the institutionalization and the relevance of the Psychosocial Care Network (RAPS), taking into account health from an expanded conception, which covers the guarantee of fundamental rights, citizenship, the democratization of access to health and the promotion of autonomy for this population. Still, from a critical criminological, penal, constitutional, and criminal procedural perspective, the founding and structuring elements of the security measure were analyzed, such as dangerousness, improper absolution, and the legal nature of the institute. In this sense, it was found that the criticisms raised in relation to the main dogmatic aspects that compose the hospitalization of the security measure also reached ambulatorial treatment, making it possible to understand that despite being executed in freedom, it is essentially a penal policy that violates a series of rights of people diagnosed with psychopathology. Also the execution of the ambulatorial security measure was examined and it was found that the care provided to the subjects is very close to the inclusive model proposed by the Psychiatric Reform, but its association with the Judicial Branch through the security measure disrespects a series of constitutional principles and proposals of the Psychiatric Reform, as it presents a sanction of a discriminatory character to this population, distancing itself from a public health policy and approaching an exclusively criminal policy. Based on these findings, a proposal for an inclusive model was elaborated, based on the current constitutional framework, penal and procedural penal guidelines, criminological critics, parameters in mental and collective health, models of deinstitutionalization and dehospitalization and, above all, in the search for concretization of an interdisciplinary work that covered the Judicial Branch, but that started from the demands of guaranteeing the fundamental rights of citizens diagnosed with psychopathology.